Subject Files of Riina Kionka
The collection of subject files was created by Radio Free Europe/Radio Liberty Research Institute analyst Riina Kionka. The materials cover the period from 1951 to 1993; most of the documents deal with the second half of the 1980s. The emphasis is on the Baltic Soviet Socialist Republics, especially Estonia, and only a small part concerns the Soviet Union in general, Eastern Europe, and other parts of the world. Riina Kionka was particularly interested in the emergence of new political parties, organizations, and movements in Estonia, which started after the beginning of changes in the Soviet Union in 1986. Among the documents should be particularly mentiond those on MRP-AEG (Estonian Group for Publishing the Molotov-Ribbentrop Pact), EVVA (Center for Helping Imprisoned Estonian Freedom Fighters), ERSP (Estonian National Independence Party), ERL (Estonian Green Movement), Popular Front, Citizens Committee’s, etc. Kionka has collected clippings from major newspapers in the Estonian Soviet Socialist Republic and central newspapers of the Soviet Union as well as from Swedish, Finnish, and German dailies. From other published material are worth mentioning Baltic Area Situation Reports from 1986-1987, 10 issues of ABN Correspondence (Bulletin of the Antibolshevik Bloc of Nations), and 5 issues of MRP-AEG Info-bulletin. One can also find news of major news-agencies and reports from Estonia. Most studied events are congresses of EKP (Estonian Communist Party), Gorbachev’s visit to Estonia in 1987, BATUN (Baltic Appeal to the United Nations), Baltic Peace and Freedom Cruise, and the nuclear catastrophe in Chernobyl. Last but not least, Kionka has researched economic issues and Soviet's terror and violation of human rights in the Estonian Soviet Socialist Republic. Accruals not expected